Investigating the Beliefs about Self of College Students in Solving Mathematical Problem - Riny Arviana (Universitas Cokroaminoto Palopo, 2019)
Human life is about an entity which always experiences the changes. Each sector of our life involving education, technology, economics, and social will be advanced gradually. These advancements let everyone to encounter the new problems or challenges for sure. Knowing this fact, ability in solving a problem is a must for us to have. The process of solving problem is influenced by several factors, like belief which is called belief system in mathematics education. Mathematics education is assumed to be able to grow and enhance one’s beliefs system in solving a problem. This research is a case study which concerns a part of beliefs system namely beliefs about self. This study aimed to investigate the beliefs about self of college students who are 18-22 years old in solving mathematical problem. Four voluntary participants were given mathematical problem and interviewed separately. The result shows that each participant has beliefs about self which is positive or negative oriented. One of the factors promoting the beliefs about self is experience. It is recommended to conduct a similar study with larger sample.